Literacy Instruction in General Education Settings: A Call to Action. (September 2019) - Toews, Samantha Gross; Kurth, Jennifer A.
While legislation and research have promoted inclusive education and the importance of literacy instruction for students with extensive support needs, the majority of literacy instruction research continues to occur in separate self-contained special education settings. This article is a call to action to the educational research community to elicit research on literacy instruction strategies, including collaborative planning, teaching, and material preparation related to grade-level general education curriculum in general education school settings. Findings from current research on literacy instruction in separate special education and general education settings are presented. Suggestions for future research and action are discussed.